Understanding the dispersion and assembly of bacterial cellulose in organic solvents - Ferguson,A; Khan,U; Walsh,M; Lee,KY; Bismarck,A; Shaffer,MS; Coleman,JN; Bergin,SD (Biomacromolecules, 2016)
The constituent nanofibrils of bacterial cellulose are of interest to many researchers because of their purity and excellent mechanical properties. Mechanisms to disrupt the network structure of bacterial cellulose (BC) to isolate bacterial cellulose nanofibrils (BCN) are limited. This work focuses on liquid-phase dispersions of BCN in a range of organic solvents. It builds on work to disperse similarly intractable nanomaterials, such as single-walled carbon nanotubes, where optimum dispersion is seen for solvents whose surface energies are close to the surface energy of the nanomaterial; bacterial cellulose is shown to disperse in a similar fashion. Inverse gas chromatography was used to determine the surface energy of bacterial cellulose, under relevant conditions, by quantifying the surface heterogeneity of the material as a function of coverage. Films of pure BCN were prepared from dispersions in a range of solvents; the extent of BCN exfoliation is shown to have a strong effect on the mechanical properties of BC films and to fit models based on the volumetric density of nanofibril junctions. Such control offers new routes to producing robust cellulose films of bacterial cellulose nanofibrils.